Frost Dynamics of Sagebrush Steppe Soils. Issue 5 (22nd September 2016) - Roundy, Bruce A.; Madsen, Matthew D.
Abstract : Core Ideas: Rangeland restoration seedings may sometimes fail due to frost damage. Seed coatings could delay seed germination until spring. Frost dynamics were characterized by soil temperatures on 14 sagebrush steppe sites. More than 60 frost periods occurred at 2‐cm depth from fall to spring. Freezing began in late October and ended in March. Sagebrush ( Artemisia spp.) steppe rangelands in the western United States are converting to weedy landscapes after large‐scale wildfires. To restore ecosystem function, perennial grasses, shrubs, and forbs are sown in fall after summer wildfires or in association with mechanical fuel reduction projects. Recent research has indicated that seeds may germinate too soon after fall sowing and seedlings suffer high mortality from frost during the winter. To help determine the length of germination delay needed to avoid seedling frost mortality and to help guide frost‐tolerance experiments, we analyzed fall to spring soil temperatures from 2010 to 2014 on six sagebrush–bunchgrass sites and eight woodland sites where conifers had invaded sagebrush communities. Soil temperatures were measured using thermocouples attached to microloggers, with stations placed in untreated, prescribed burned, and mechanically treated plots. Soil freezing differed with site, year of measurement, and soil depth but was relatively unaffected by fire and mechanical fuel reduction treatments. The 2‐cm depth experienced much more freezing than lower depths (14–29 cm) and had >60 freeze–thaw cycles from late October into late March. Although maximum continuously frozen periods ranged from 11 to 45 d, most frost periods were <1 d long. Additional field and laboratory research is needed to determine the effects of different seed coatings on germination delay and frost dynamics on seedling mortality to best avoid frost mortality.